Thirteen Pancarpal Arthrodeses Using 2.7/3.5 mm Hybrid Dynamic Compression Plates - Li, A.; Gibson, N.; Carmichael, S.; Bennett, D. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
Thirteen pancarpal arthrodeses were performed in eleven dogs at the University of Glasgow Veterinary School. All of the animals were presented as referral patients. Two of the eleven dogs had the procedure carried out in both carpi. The arthrodeses were carried out using a 2.7/3.5 mm hybrid dynamic compression platea. The animals were between 1 year and 11 years of age. Their weight ranged from 15 kg to 38 kg. Two cases had associated soft tissue trauma/infection prior to the surgery; these two dogs together with one other developed post-operative soft tissue problems. The soft tissue problems had resolved by the time of radiographic arthrodesis. The plate was removed in three cases due to persistent lameness. The animals were followed up for a period of at least eight weeks postoperatively; the maximum follow-up time was fourteen months. Arthrodesis occurred in all thirteen antebrachio-carpal joints. The hybrid plate can thus be recommended for carpal arthrodesis in the dog and has many advantages over a conventional dynamic compression plate.Pancarpal arthrodeses were performed in dogs using custom made 2.7/3.5 mm Hybrid Dynamic Compression Plates instead of conventional AO/ASIF Dynamic Compression Plates (DCP). The implantation of the plates was facilitated by their profile and the usage of smaller 2.7 mm screws in the metacarpal regions. All of the carpi went on to full arthrodesis within the follow-up period. The rate of complications associated with the use of this plate compares favourably against previous similar studies using the conventional DCP.
Keywords: Canine; pancarpal arthrodesis; hybrid dynamic compression plate